Vehicle Routing Problem Dengan Time Window Untuk Multiple Product Dan Multiple Route Menggunakan Algoritma Sequential Insertion - Putri, Dita Ayu Pratama (Jurnal Teknik Industri, 2017)
In this article is related to implemented a method in order to solve vehicle routing problem (VRP) for mineral water distribution activity from depot to customers which has particular constraints such as variant of product that has to be load at a vehicle (multiple product), vehicle’s capacity and time window of each customers. One of the company’s vehicle have 64 customers that must be visited in 6 days so there is a few route has been developed (multiple route). The constraint that set up sustained there might be few customers missed to be visited during horizon plan. Sequential Insertion Algorithm which is one of heuristic method for Vehicle Routing Problem with Time Window is choosen to built a vehicle routing solution. The result from this study show that this method in particular conditions and constraints give a better solusion than the company actual routes. Moreover, in this article, the comparasion of distance and completion time between solution route and actual route, and also the saving in cost is also analyzed. The using of Sequential Insertion Algorithm in this article can be used and applied because its perform an optimal result.